Efficacy of the anterograde calcaneo-stop method in the management of flexible flatfoot in children - Alexeevich, Koshman G.; Direcksze, Naveen D. K. N.; Dineshkumar, Prithvi A.; Yogarajah, Kirisayon; Rumi, Mohamed A. A.; Ariyarathna, Jayasooriya P. D. I.; Vitharana, Arjuna P. (International Journal of Research in Orthopaedics, 2025)
Background: Flexible flatfoot is one of frequent foot deformity among pediatric population. The calcaneo-stop procedure has been reported to be effective in short-term studies when conservative treatment is not successful. The aim of this study to evaluate the efficacy after removal of screws following the anterograde calcaneo-stop procedure in the treatment of flexible flatfoot in children. Methods: This retrospective study consists of 260 calcaneo-stop procedures performed from the period of January 2016 to December 2024 in 65 patients (130 anterograde calcaneo-stop surgeries and 130 removals of calcaneo-stop implant surgeries), which were evaluated clinically, and instrumental diagnostic techniques such as radiography, photoplantography and pedobarography were implemented. The inclusion criteria of this study consist of patients with symptomatic flexible flatfoot, patients with ages from 6 to 14 years, patients with informed consent, patients with negative Wynne-Davies joint hypermobility test and the exclusion criteria of this study includes the following; patients with ages below 6 years and above 14 years, the time elapsed of 3 years after screw implantation, patients with other skeletal deformities, patients without informed consent. Results: Out of the 130 surgical interventions performed on bilateral flexible flatfoot, which were evaluated in 65 patients after removal the screws following the anterograde calcaneo-stop procedure, revealed no signs of loss correction; which were further evaluated by radiography, photoplantography and pedobarography. Conclusions: The calcaneo-stop procedure is the least invasive and simplest surgical treatment for symptomatic flexible flatfoot in children. The collected data indicated a sufficiently high efficiency of anterograde calcaneo-stop method in the treatment of flexible flatfoot in children.